Religion in maternal health care: case report - Zangão,Maria (2022)
Abstract Introduction: Religion plays a fundamental role in the cultural life of different groups and places that is integrated in complex ways into the beliefs, actions, and experiences of the faithful. Objective Develop a proposal for a care plan with emphasis on interventions carried out according to religious beliefs and their decisions before a pregnant patient. Methods: Case study organized according to the guidelines of the CAse REport referring to a female user, 26 years old, 41 weeks pregnant, and Jehovah's Witness. For data collection, the Theoretical Model of Nancy Roper (model of activities of daily living) was used and for the elaboration of the nursing care plan, the ICNP and NIC taxonomy was used. Results: Based on the initial assessment, 17 nursing diagnoses were identified, of which two diagnoses stood out as being relevant to the issue of religion: Current anxiety and present moral anguish. Conclusion Religious beliefs often lead to ethical conflicts in blood transfusion decisions, as there are religions that do not allow it and in a case of life or death, health professionals end up having to decide whether they respect the patient's wishes or if your professional deontology, however, there are more and more alternatives to a blood transfusion, where we can reduce this ethical dilemma.